Strategi Mengatasi Problematika Mutu Pembelajaran Melalui Merdeka Belajar di Lembaga PAUD - Ida Destariana Harefa; Eny Suprihatin (Universitas PGRI Semarang, 2023)
AbstrackEarly Childhood Education (ECCE) has an urgent role in the world of education. As an ECCE institution, its role is to ensure the quality of learning and educational services according to the standards and characteristics of child development. The problem that occurs today is in terms of quality or quality of learning. This type of research uses literature studies by collecting data through various book materials, articles, and research results related to research studies which are then analyzed. After conducting the screanning process, 20 articles and 4 books were selected as the final review. Data analysis techniques using content analysis methods aim to describe and infer the content of data sources. The result of deepening the literature is: there are still many ECCE products that have not met the established standards. In learning, it often happens that teachers do not carry out their roles and functions. Teachers explain a lot and still use a teacher-centered system. The assignment system tends to be passive so that children find it difficult to express opinions, lack of collaboration between teachers and children. As a result, teachers are unable to bring about change to develop creative learning models for early childhood. The strategy to overcome problems in the world of education is to improve the quality of learning. The government made a learning strategy by changing the child-centered curriculum, through Freedom to Play or Freedom to Learn.Keywords: Quality of Learning; Independent Learning; Teachers; ECCE.AbstrakPendidikan Anak Usia Dini (PAUD) memiliki peran mendesak dalam dunia pendidikan. Sebagai lembaga PAUD berperan menjamin mutu pembelajaran dan layanan Pendidikan sesuai standar dan karakteristik perkembangan anak. Problematika yang terjadi saat ini ada pada segi kualitas atau mutu pembelajaran. Jenis penelitian menggunakan studi literatur dengan mengumpulkan data melalui berbagai bahan buku, artikel, dan hasil penelitian yang berhubungan dengan kajian penelitian yang kemudian dianalisis. Setelah melakukan proses screanning dihasilkan 20 artikel dan 4 buku yang dipilih sebagai peninjauan akhir. Teknik analisis data menggunakan metode analisis isi bertujuan untuk menguraikan dan menyimpulkan isi dari sumber data. Hasil dari pendalaman kepustakaan adalah: masih banyak produk PAUD yang belum memenuhi standar yang ditetapkan. Dalam pembelajaran sering terjadi guru tidak melaksanakan peran dan fungsinya. Guru banyak menjelaskan dan masih mengggunakan sistem berpusat pada guru. Sistem penugasan cenderung pasif sehingga anak sulit menyampaikan pendapat, kurangnya kolaborasi antar guru dan anak. Akibatnya, guru tidak mampu membawa perubahan untuk mengembangkan model pembelajaran kreatif bagi anak usia dini. Strategi untuk mengatasi permasalahan dalam dunia pendidikan yaitu dengan meningkatkan mutu pembelajaran. Pemerintah membuat strategi pembelajaran dengan mengubah kurikulum berpusat pada anak, melalui Merdeka Bermain atau Merdeka Belajar.Kata Kunci: Mutu Pembelajaran; Merdeka Belajar; Guru; PAUD.